Inmersive Marketing: Impact on Roblox services brands - Uribe, Clara (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2026)
The technological revolution and the rise of immersive platforms are transforming marketing strategies, even for service brands, by offering interactive experiences and connections with young people in in immersive gaming environments. This study applies a mixed-methods methodology to analyze the immersive marketing strategies of Spotify and McDonald's on Roblox and the preferences of their target audiences. The findings reveal similarities in the immersive strategies, tailored according to brand objectives and values, connecting the virtual with the physical. It also highlights young gamers' preference for online purchases, motivated by the experiences they have in the virtual world.